1983
DOI: 10.1073/pnas.80.23.7192
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium NMR as a structural probe for micelle-associated carbohydrates: D-mannose.

Abstract: Residual quadrupole splittings for deuterons on perdeuterated a-and (3-D-mannose oriented in a potassium laurate liquid crystal have been measured. Multiple quantum two-dimensional NMR spectroscopy at high magnetic field is used to gain sufficient resolution to assign splittings to specific sites within these molecules. The assigned splittings are interpreted in terms of molecular geometries and preferred orientations of the molecules relative to the surface of the potassium laurate micelles that make up the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Already during the 1980s, Prestegard and co-workers were exploring orientational and conformational preferences of mono- and disaccharides in membranelike environments using either potassium laurate micelle systems or the more bilayerlike cesium perfluorooctanoate micelles. In particular, NMR deuterium quadrupolar splittings of labeled carbohydrates were used to interpret experimental observations; both molecular orientation and conformation were adjusted in the search procedure. For organic molecules in general and carbohydrates in particular, RDCs are a source of additional NMR observables that add knowledge about various conformational processes occurring in solution. …”
Section: Introductionmentioning
confidence: 99%
“…Already during the 1980s, Prestegard and co-workers were exploring orientational and conformational preferences of mono- and disaccharides in membranelike environments using either potassium laurate micelle systems or the more bilayerlike cesium perfluorooctanoate micelles. In particular, NMR deuterium quadrupolar splittings of labeled carbohydrates were used to interpret experimental observations; both molecular orientation and conformation were adjusted in the search procedure. For organic molecules in general and carbohydrates in particular, RDCs are a source of additional NMR observables that add knowledge about various conformational processes occurring in solution. …”
Section: Introductionmentioning
confidence: 99%
“…This has been successfully achieved using liquid crystals formed by bicelles (2), bacteriophages (9, 10), or purple membranes (11) as the orienting medium. Although the mechanism of molecular alignment in the liquid crystal solutions is still under debate, it has been proposed that, in the case of micelles and neutral bicelles, the alignment force can be of steric origin (12,13). Other types of mechanism cannot be ruled out, since there is evidence of the influence of electrostatic interactions when using charged bicelles (14).…”
mentioning
confidence: 99%
“…74, 4.93, 5.08, 5.15, 5.19, and 5.26 ppm, respectively. Therefore, the H-1/C-1 signal at 4.74/103.0 ppm indicated that the residues should be assigned to (1 → 3)-linked ␤-d-mannopyranosyl (Patra et al, 2013;Prestegard, Miner, & Tyrell, 1983). However, the anomeric chemical shifts of H-1/C-1 at 5.08/104.6, 5.15/104.8, and 5.19/96.6 ppm should be assigned to (1 → 3)-linked ␣-d-mannopyranose residues (Cui, 2005;Ližičárová, Matulová, Machová, & Capek, 2007;Takahashi, Kudoh, Okawa, & Shibata, 2012).…”
Section: Mannosyl Residuementioning
confidence: 98%